2014
DOI: 10.35790/ebm.2.2.2014.5518
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Bakteri Pada Depot Air Minum Isi Ulang Di Kota Manado

Abstract: Water is a chemical compound that has a very important role for the life of humans and other living creatures but also serve as a medium of transmission of diseases. Refillable drinking water has become a common choice for the people in Indonesia, including in the city of Manado. One of the diseases caused by drinking poor quality water is diarrhea. To determine the condition of the contaminated refillable drinking water, a research or clinical testing in the laboratory is needed. The purpose of this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Hasil penelitian di dua lembaga ini menunjukkan bahwa air minum isi ulang secara bakteriologis telah terkontaminasi bakteri Coliform, E. Coli, salmonella, sedangkan secara kimiawi sampel air terdeteksi mengandung logam berat cadmium. 8 Disamping itu penelitian yang dilakukan oleh Malisa di Kecamatan Seberang Ulu Kota Palembang, menyatakan bahwa 76% dari produk air minum dihasilkan oleh DAMIU tidak memenuhi syarat kesehatan dan ditemukan bakteri coliform. 9 Diare merupakan salah satu penyakit yang disebabkan oleh air minum yang telah terkontaminasi oleh mikroorganisme, dan diare merupakan salah satu penyakit di Indonesia dengan angka kejadian tinggi khususnya pada bayi dan balita.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Hasil penelitian di dua lembaga ini menunjukkan bahwa air minum isi ulang secara bakteriologis telah terkontaminasi bakteri Coliform, E. Coli, salmonella, sedangkan secara kimiawi sampel air terdeteksi mengandung logam berat cadmium. 8 Disamping itu penelitian yang dilakukan oleh Malisa di Kecamatan Seberang Ulu Kota Palembang, menyatakan bahwa 76% dari produk air minum dihasilkan oleh DAMIU tidak memenuhi syarat kesehatan dan ditemukan bakteri coliform. 9 Diare merupakan salah satu penyakit yang disebabkan oleh air minum yang telah terkontaminasi oleh mikroorganisme, dan diare merupakan salah satu penyakit di Indonesia dengan angka kejadian tinggi khususnya pada bayi dan balita.…”
Section: Pendahuluanunclassified
“…Hasil penelitian di dua lembaga ini menunjukan bahwa air minum isi ulang terkontaminasi bakteri coliform, E. Coli, Salmonella. 8,20 E coli yang terkandung pada air dapat dijadikan petunjuk bahwa air telah tercemar air oleh kotoran manusia. 21 Mikrobamikroba ini dapat menyebabkan sakit yang lebih parah, termasuk infeksi intestinal, hepatitis, demam tifoid dan kolera.…”
Section: Hubungan Fasilitas Cuci Tangan Damiu Dengan Kualitas Bakteriologis Air Minum Hasil Pengolahan Depot Air Minum DI Kabupaten Ogan unclassified
“…found that 663 million people still had difficulty accessing clean water In connection with this water crisis, it is predicted that in 2025 nearly twothirds of the world's population will live in areas that experience water shortages 1 . The forecast was reported by the World Water Assessment Program (WWAP), formed by the United Nations Educational, Scientific, and Cultural Organization Regarding Indonesia, in 2012 the Indonesian Institute of Sciences (LIPI) recorded that Indonesia was ranked the worst in the service of the availability of clean water and suitable for consumption in Southeast Asia 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of these pathogens indicates that poor hygiene and sanitation also maintenance of equipment related to the provision of drinking water. (Rumondor, Porotu'o and Waworuntu, 2014)Data on the relation between the contaminated depots and diarrhea cases in Pagatan area is not yet available and the weakness of drinking water surveillance by the local health office is the basis of this study held.…”
Section: Introductionmentioning
confidence: 99%